2012
DOI: 10.1007/s11250-012-0290-2
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of bovine viral diarrhea infection in Yaks (Bos grunniens) on the Qinghai-Tibetan Plateau of China

Abstract: The seroprevalence of bovine viral diarrhea virus (BVDV) infection in yaks was investigated in Qinghai and Tibet of China during the year 2011. A total of 549 (Tibet 287, Qinghai 262) serum samples was collected from Tibet and Qinghai and were examined for BVDV p80 antibody by ELISA. The results of the experiment showed that 145 (53.65 %) of Tibetan samples and 189 (72.14 %) of Qinghai's samples were positive for BVDV. The observations of the present study suggest that bovine viral diarrhea is common in yaks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
0
13
1
Order By: Relevance
“…These results are within previously reported ranges, but the seroprevalence of beef cattle was greatly increased in our study, which was probably due to the frequent movement of calves because of the rapid expansion of the beef industry. In addition, the seroprevelance among yaks in Qinghai province (51.36%) and Tibet (30.92%) in this study were lower than previously reported (72.14% and 53.65%, respectively) [ 33 ]. We propose the following reasons for these differences: (i) the samples came from different regions; and (ii) in some regions, yaks vaccinated with live CSFV vaccine might have improved the false positive rate in the cited previous reports or played a role in the control of BVDV spread leading to the later decrease in the seropositive rates in this study.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…These results are within previously reported ranges, but the seroprevalence of beef cattle was greatly increased in our study, which was probably due to the frequent movement of calves because of the rapid expansion of the beef industry. In addition, the seroprevelance among yaks in Qinghai province (51.36%) and Tibet (30.92%) in this study were lower than previously reported (72.14% and 53.65%, respectively) [ 33 ]. We propose the following reasons for these differences: (i) the samples came from different regions; and (ii) in some regions, yaks vaccinated with live CSFV vaccine might have improved the false positive rate in the cited previous reports or played a role in the control of BVDV spread leading to the later decrease in the seropositive rates in this study.…”
Section: Discussioncontrasting
confidence: 83%
“…For large-scale farms, the average seroprevalence rate reached 92.5% among dairy cows and 29.8% among beef cattle in Fujian province in southern China [ 32 ]. In western China, the seroprevalence of yaks was reportedly 53.65% in Tibet and 72.14% in Qinghai province [ 33 ]. The positive ratio of neutralization Ab in water buffalo averaged 17.25% in some areas [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, bovine tuberculosis is a chronic bacterial disease of animals and humans and is a major infectious disease among cattle, other domesticated animals, and certain wildlife populations in a large number of countries (Gumi et al, 2012;Schiller et al, 2010). In Tibet, this disease remains a serious public health problem and causes significant economic losses in the production of yaks (Gao et al, 2012). Moreover, yaks must survive inadequate feeding during the long cold season (October to May), which results in malnutrition and low production (Miller, 1996), because of the herbage deficiency that occurs with the pure grazing of the traditional farming system.…”
Section: Introductionmentioning
confidence: 99%
“…However, information on the effects of dietary CP supplements on early-weaned yaks is scarce. Moreover, tuberculosis is a serious public health problem and causes significant economic losses in yak production in Tibet (Gao et al, 2012). Vaccination is a low-cost and effective strategy for the prevention and therapeutic reduction of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first serological detection of BVDV infection in yaks in Qinghai, China [25], numerous investigations have documented a seroprevalence of BVDV antibodies ranging from 0.56% to 72.14% [26-29]. While a molecular epidemiological survey of BVDV in yaks has been conducted in the Himalayan region [30], it is unclear if a similar situation of BVDV infections in the Chinese yaks.…”
Section: Introductionmentioning
confidence: 99%